FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN AYAM POTONG MERAUKE DI PASAR WAMANGGU DISTRIK MERAUKE KABUPATEN MERAUKE - Fibiantoro, Imam; Widyantari, Ineke Nursih; Nurliah, Nurliah (Agriculture Faculty of Flores University, 2025)
Wamanggu Market, the largest trading center in Merauke District, is under the careful management of the local government. This ensures that the market operates smoothly and efficiently, offering a variety of commodities and attracting numerous sellers and buyers, particularly those interested in broiler meat. For consumers purchasing broiler meat, there are several key considerations to keep in mind, such as color, weight, and meat elasticity. The research was conducted over two months, January to February 2023, to identify the variables that influence the behavior of slaughter chicken buyers. This study is quantitative descriptive. The place of research is Wamanggu Market. The research population is residents of Merauke District. The number of samples taken was 44 chicken buyers were taken purposively. The research data included primary data obtained by conducting interviews, observations, and questionnaires and secondary data obtained from literature, the internet, and BPS. The data analysis used in the research is multiple linear regression. The study found that cultural, personal, and psychological factors influence buying broiler chicken. However, psychological factors are the most influential factor in buying broiler meat.